THE EFFECTIVENESS OF THE STAD AND JIGSAW MODELS IN IMPROVING THE VOLLEYBALL PASSING SKILLS OF STUDENTS IN GRADE VIII AT SMPN 3 DARANGDAN PURWAKARTA - Adhari, Naufal Ardi; Achmad, Irfan Zinat; Nasution, Nana Suryana (Jurnal Penjaskesrek, 2025)
One of the efforts in the physical education learning process to improve students' abilities is through volleyball learning by learning basic passing techniques. This study aims to examine the effectiveness of the application of the STAD and Jigsaw cooperative learning models in improving volleyball passing abilities in class VIII students of SMPN 3 Darangdan Purwakarta. The research method used is a quantitative approach with an experimental design. The results of the analysis showed an increase in posttest scores in the class with the STAD learning model, with an average N-Gain score of 0.760 (> 0.7) and an N-Gain percentage of 76.02%, which is classified as effective. Meanwhile, the class with the Jigsaw learning model obtained an average N-Gain score of 0.437 (< 0.7) and an N-Gain percentage of 43.69%, which is included in the fairly effective category. Based on these findings, it can be concluded that both learning models have an effect on improving volleyball passing abilities, with the effectiveness of the STAD model being higher than the Jigsaw model.